Mechanical Traction Techniques for Long-Gap Esophageal Atresia: A Critical Appraisal - Nasr, Ahmed; Langer, Jacob C. (European Journal of Pediatric Surgery, 2013)
Background Long-gap esophageal atresia (EA) represents a challenging problem for pediatric surgeons, and a large number of techniques and approaches have been proposed. One of the more recent, initially published by Foker, is the use of mechanical traction to accelerate the growth of the esophageal ends and permit earlier primary anastomosis. The purpose of this study is to critically evaluate the existing literature on this topic and to compare the Foker technique to the more conventional delayed primary anastomosis.Methods A systematic review and cumulative meta-analysis was performed, including all articles describing the Foker technique or delayed primary anastomosis. Primary outcome was complications, and secondary outcome was time to final anastomosis.Results Six articles on the Foker procedure met the criteria for inclusion. None were prospective or randomized. These articles represented 71 infants undergoing the Foker procedure, which were compared with 451 children from 44 studies utilizing delayed primary anastomosis. The Foker procedure was associated with a significantly lower risk of complications (leak, stricture, and gastroesophageal reflux), and with a significantly shorter time to definitive anastomosis.Conclusions The use of mechanical traction appears to be at least as effective as delayed primary anastomosis for the management of long-gap EA. Future prospective studies and the establishment of a prospective registry are required to further elucidate this issue.
Keywords: esophageal atresia; mechanical traction; critical appraisal